Technology and economic analysis of urban waste potential (case study of Jatibarang landfill). Issue 1 (January 2021) - Saleh, M; Sinuraya, E W; Denis, D; Gregorius, P; Hardian, E
Abstract: The high volume of waste produced by both industry and society is common in almost all cities. For this reason, it is necessary to control the increase in the volume of waste and its implications for the environment. The scenario used in this research is to design a power plant that can be used to control the increase in the volume of waste, namely PLTSa (Waste Power Plant). PLTSa uses organic waste from trash to generate clean, renewable energy, powering communities, and reducing emissions. At the PLTSa, the organic waste is fed into a digester tank, where it is converted into methane by bacteria. The gas is then sent to the waste power plant, which generates 0.9 MW of power. The PLTSa supports the Indonesian government's plan to increase electricity in the country by 35, 000 MW from 2015 to 2019, and for 25% of that electricity to be generated from renewable sources. The government's plan was in response to a shortage of electricity generation capacity as demand in the country grows. The data analysis method used to analyze the research data is an analysis using the IPCC Inventory software and the LFGcost-Web Landfill Gas Emission Model (LandGEM). Data analysis results in the form of projections of biogas potential and electrical energy will be used to build PLTSa. Waste-to-energy generation is being increasingly looked at as a potential energy diversification strategy, especially in Indonesia and PLTSa (Waste Power Plants) in several cities in Indonesia.